Gene Transmission, Growth, and Exogeneous Growth Hormone Expression of G2 Transgenic Betta Fish (Betta imbellis) - Nadia Ayuningthias; Hasan Nasrullah; Dinar Tri Soelistiyowati; Eni Kusrini; Alimuddin Alimuddin (Faculty of Fisheries and Marine Universitas Airlangga, 2021)
Highlight ResearchThe F2 of GH-transgenic B. imbellis was successfully producedThe transgene inheritance by the F2 fish was more than 90%The growth and body size of transgenic fish was significantly higher than controlF2 fish reached a larger body size in a shorter period compared to the F1 AbstractIn our previous research, we had successfully produced G0 and G1 Pangasianodon hypophthalmus growth hormone (PhGH) transgenic B. imbellis, native ornamental betta from Indonesia, which its giant-sized variant has valuable price for the breeders. The G0 and G1 transgenic (TG) fish showed higher growth rate and body size compared to the non-transgenic (NT) fish. The study was aimed to produce and evaluate the consistencies of transgene transmission and expression in G2 generation. The growth rate and body size between TG and NT fish was also compared. The G2 generation was produced using crosses between TG and NT G1 fish: â™‚TG í— â™€TG, â™‚TG í— â™€NT, â™‚NT í— â™€TG, and â™‚NT í—â™€ NT. Fish were reared for 12 weeks, and transgene detection was performed using the polymerase chain reaction method (PCR) on isolated DNA from the caudal fin clips. The endogenous and exogenous GH expression analysis was conducted using the quantitative real-time PCR (qPCR) method. The results showed that the inheritance of the GH transgene by the G2 fish was more than 90% in all transgenic crosses. Endogenous GH was expressed at the same levels in the brain of TG and NT fish, but the exogenous GH expression was highly detected only in the TG fish. The G2 transgenic fish had a higher specific growth rate, up to 31%, compared to the control. The body length of TG crosses were 23âˆ’35% higher and had 111âˆ’135% higher body weight compared to NT fish. These results showed a promising approached in mass-producing stable lines of giant-sized betta using the GH-transgenic technology.